Indigenous-Owned Pastoral Land Forestry Carbon Biosequestration and Bioenergy Options in Arid, Salt-Affected Western Australian Regions - McHenry, Mark; Anwar-McHenry, Julia (Nova Science Publishers, 2013)
This research comprises a technical and economic feasibility study of geoengineering and revegetating 1,500 ha on an Indigenous-owned pastoral lease in an arid region (<250 mm mean annual rainfall) in the Mid West Region of Western Australia for forestry carbon biosequestration and bioenergy projects. A single tree species, Eucalyptus camaldulensis, an indigenous species of the region was used in two modelled scenarios. The carbon biosequestration and NPC (8% p.a. real discount rate) was modelled over 15 years, yielding an equivalent mitigation cost of AUD15.34 tCO2-e-1, assuming the total biosequestration (185,635 tCO2-e) was forward sold in year 0 in the first scenario. In the second scenario the stand was the primary feedstock for a biorefinery producing activated carbon, renewable electricity, and biodiesel produced from 20 t day-1 (16% moisture) E. camaldulensis, with harvesting commencing in the sixth year after stand establishment. The final total biosequestration for both the unharvested and harvested stand scenarios were modelled as identical in the 15th year. The NPV of the biorefinery was modelled separately from stand biosequestration also discounted at 8% p.a. Depending on the mitigation assumptions, and the commercial costs/prices of inputs/outputs over the 15 years, the biorefinery NPV ranged from slightly below zero to AUD6.5 million, and mitigated a further 74,000tCO2-e.